Behavior of group of geosynthetic encased granular piles with tire chips- aggregates mixture under static and cyclic loading – A model study - Pradeep N.M.; Kumar S.; Gupta S.; Nishant M. (My University, 2025)
The current study addresses the dual challenges of improving the performance of soft soil beds subjected to static and cyclic stresses and managing the environmental impact of waste tire disposal. This research contributes valuable insights into the sustainable use of recycled tire chips in granular pile construction, coupled with the efficacy of combi-grid encasement for improved soft ground under static and cyclic loading conditions. A series of laboratory model tests were carried out on a group of granular piles to examine the principal parameters, such as the selection of geosynthetic materials and cyclic loading characteristics, including cyclic loading amplitude (qca) and cyclic loading frequency (f). The granular pile composition consists of (25% tire chips + 75% aggregates). The performance of granular piles on improved ground is assessed based on the settlement reduction ratio (Sc,r), accumulation of excess pore water pressure (Pexc), and stress concentration ratio (n). The key findings from static model tests are that the load-bearing capacity is significantly increased with installing a group of ordinary granular piles (= 58%) and substantially increased with combi-grid encasement (= 335%). The effectiveness of ordinary granular piles (OGP) in enhancing the performance of a soft soil bed becomes greater when subjected to lower cyclic loading frequencies (f) and smaller cyclic loading amplitudes (qca). The incorporation of combi-grid encasement greatly enhanced the cyclic performance of a group of granular piles by substantially minimizing cyclic-induced settlement (Sc) across both principle parameters f and qca. This study also examines the increased cyclic stresses on the improved soft bed, resulting in the accumulation of excess pore water pressure (Pexc) development, which is reduced to a greater extent with the help of combi-grid encasement across both principle parameters. © 2024 Elsevier Ltd